Nilai Gizi serta Daya Terima Biskuit dengan Penambahan Tepung Ikan Layang (Decapterus russelli) dan Ikan Selar (Caranx SP) (The Nutritional Value and Acceptability of Biscuits with the Fish Addition of Indian Scad (Decapterus russelli) and Trevally (Caranx. sp) Fishmeal) - Mudjajanto, Eddy Setyo; Kholilah, Wiwin; Amaliah, Nurillah (Jurnal Sains Terapan : Wahana Informasi dan Alih Teknologi Pertanian, 2015)
The general purpose of this research was to study the nutritional value and acceptability of biscuits with the addition of Indian Scad (Decapterus russelli) and Trevally (Caranx sp) fishmeal. This study was divided into two stages: a preliminary study and further research. Generally, Indian Scad fishmeal has 11.65% moisture content, 7.94% ash, 89.26% protein, 0.34% fat and 36.66 ppm iron, and the yield is 15.96%. However, the Trevally has 7.34% moisture content, 0.53% fat, 89.86% protein, 10.92% ash, 18.05% iron, and the yield is 12.65%. Based on the state of fat, ash, iron and yield, the chosen fish to be further tested was the Indian Scad. Nutrient content of controlled and selected biscuits ranged from 2.33%-3.93% water content, 1.61%-2.82% ash, 6.60%-20.01% protein, 18.61%-21.90% fat, 58.51%-70.01% carbohydrates, 928.28-933.92 ppm iron, and 0.00-3.14 mg O2/100 g peroxide. The content of the biscuit met the ISO standard No. 01-2973-92 except for the levels of fat and carbohydrates which were less than the standard. Nutrient loss of controlled and selected biscuits during the processing were of 72.3% and 83.45% water content, 0.61% and 0.36% ash, 4.65% and 1.33% protein, 0.09% and 0.59% fat, 0.46% and 0.47% iron. The results showed that the addition of Indian Scad fishmeal was significantly affected on the moisture, ash, protein, fat, carbohydrates and peroxide, but had no effect on iron levels.     Keyword : fishmeal, nutritional value, indianscad, trevally